Modelling and assessment of the electric field strength caused by mobile phone to the human head - Buckus, Raimondas; Strukcinskiene, Birute; Raistenskis, Juozas; Stukas, Rimantas (Vojnosanitetski pregled, 2017)
Background/Aim. Electromagnetic field exposure is the one of the most important physical agents that actively affects live organisms and environment. Active use of mobile phones influences the increase of electromagnetic field radiation. The aim of the study was to measure and assess the electric field strength caused by mobile phones to the human head. Methods. In this paper the software “COMSOL Multiphysics” was used to establish the electric field strength created by mobile phones around the head. Results. The second generation (2G) Global System for Mobile (GSM) phones that operate in the frequency band of 900 MHz and reach the power of 2 W have a  stronger electric field than (2G) GSM mobile phones that operate in the higher frequency band of 1,800 MHz and reach the power up to 1 W during conversation. The third generation of (3G) UMTS smart phones that effectively use high (2,100 MHz) radio frequency band emit the smallest electric field strength values during conversation. The highest electric field strength created by mobile phones is around the ear, i.e. the mobile phone location. The strength of mobile phone electric field on the phantom head decreases exponentially while moving sidewards from the center of the effect zone (the ear), and constitutes 1–12% of the artificial head’s surface. Conclusion. The highest electric field strength values of mobile phones are associated with their higher power, bigger specific energy absorption rate (SAR) and lower frequency of mobile phone. The stronger electric field emitted by the more powerful mobile phones takes a higher percentage of the head surface. The highest electric field strength created by mobile phones is distributed over the user's ear.
Keywords: cellular phone; electromagnetic fields; health; head